Factors affecting use of emergency contraception among college students in Kathmandu, Nepal. - Deo,Khushbu (2019)
ABSTRACT: BACKGROUND: Adolescent and youth sexual behavior has been recognized as an important health, social and demographic concern the developing world. Unwanted pregnancy poses a big problem among young adult in developing countries. Emergency contraceptive plays vital role in reducing maternal mortality substantially and improves maternal health by avoiding unwanted pregnancy and unsafe abortion. The main objective of the study was to assess factors affecting use of emergency contraception among college students of Kathmandu. METHODOLOGY: This study is a cross sectional study conducted among 476 college students of Kathmandu, Nepal. Structured self-administered questionnaire were used. Univariate, bivariate (Chi square test) and multivariate analysis were applied for assessing association between dependent and independent variables. RESULTS: In this study, among the respondent who had heard about emergency contraceptive, 57.2% of the respondents were found to have used emergency contraceptive pills. Variables such as place of residence (AOR=0.076, p=<0.001), level of study (AOR=0.027, p=<0.001), communication about RH matter with family (AOR=7.975, p=0.002) and Knowledge on ECPs (AOR=0.021, p=<0.001) were found to be the factors that affected the use of emergency contraception among college students. CONCLUSION: Unintended pregnancy and unsafe abortion pose a major reproductive health challenge. Hence identification of the predictors that affect its use is effective in preventing unplanned pregnancy. Key Words: Emergency contraception, emergency contraceptive pills, unintended pregnancy, college students